The Use of Vascular Endothelial Growth Factor Inhibitors in Patients with Proliferative Diabetic Retinopathy - V. Yu. Evgrafov; G. R. Kudasheva (Oftalʹmologiâ, 2022)
Diabetic retinopathy (DR) have been taking a leading position among retinal disorders, causing a persistent and significant decrease in visual functions. The base of the disease is a retinal vascular microangiopathy, which induces a tissue ischemia and excessive production of vascular endothelial growth factors. The main method of treatment for this pathology is a laser photocoagulation. However, it is not always possible to perform appropriate laser photocoagulation, by that limiting its efficacy (cases of hard cataract and hemophthalmos). In addition, this type of treatment might have a number of serious complications, such as macular oedema, recurrent vitreous hemorrhages, the occurrence of fibrosis, atrophic changes in the retina, which leads to a decline in visual acuity and contrast sensitivity, worsening the visual field. Over the past 10 years, vascular endothelial growth factor inhibitors have been introduced into clinical practice, and showed their benefits in the treatment of disorders leading to a pathological angiogenesis. But due to the limited number of systematic observations, assessing the impact of these drugs, is necessary to investigate their efficacy and safety in patients with proliferative DR, in order to develop indications for their use. The purpose of the review is evaluation of the effect of vascular endothelial growth factor inhibitors on active neovascularization in patients with proliferative diabetic retinopathy. There is a literature of international clinical guidelines, randomized clinical trials with a varying level of evidence, articles and publications by groups of authors in the article.